A novel online visualization system for observing polymer extrusion foaming. (July 2016) - Peng, Xiang-Fang; Liu, Lu-Yang; Chen, Bin-Yi; Mi, Hao-Yang; Jing, Xin
Abstract: Cell nucleation and premature cell growth in extrusion foaming are critical to elaborate the morphology of final foams. These courses happen in the extrusion die which has been unknown for real extrusion foaming process. In this study, a novel visualization system was developed to online observe the cell nucleation and evolution behavior in the extrusion die. The cell evolution and real time pressure along the flow direction could also be obtained with the system. It was found that the solution pressure P solution was influential to the critical nucleation radius R cr and the nucleation rate N 0 . The higher screw rotating speed corresponded to higher P solution, lower in die N 0 and less premature cells, while higher cell density for extrude foams. In addition, premature cells with radius over critical break radius R crb would break into several small cells under sufficient stress gradient in the extrusion flow field.